Survey of the state of conservation of the Mylodon listai (Xenarthra-Mylodontidae) skin fragment from the Pleistocene of Argentina kept at the Museum of La Plata (Argentina) - Nitiu, Daniela Silvana (2016)
The aim of the present study was to assess the state of conservation of the fossilized skin fragment assigned to Mylodon listai preserved in a showcase of the Paleontology Hall of the Museum of La Plata. To this end, we conducted a volumetric aerobiological sampling both inside the showcase and in the hall to detect the presence of fungal load that could alter its preservation. We also determined the environmental parameters both inside and outside the showcase. The aerobiological sampling inside the showcase showed 3061.50 spores/m3 corresponding to 22 fungal types, while in the hall, 2283.20 spores/m3 corresponding to 14 fungal types where detected. Cladosporium was the most important type in all the sampling points. The temperatures recorded were lower than those recommended for the conservation of leather and the relative humidity values were acceptable in 70% of the record for this material.